Corruption in Social Forestry in Indonesia - Ismariana, Ema; Kusuma, Aprisep Ferdhana; Permadi, Dwiko Budi; Kartodihardjo, Hariadi; Santoso, Widodo Budi; Maryudi, Ahmad (Forestry Faculty, Universitas Hasanuddin, 2024)
Social forestry is envisioned as a governance reform to empower rural communities to improve both the forest condition and their quality of life. In Indonesia, however, its implementation has been plagued by a number of governance-related issues including corrupt practices among various actors. Drawing on programs implemented in Java, we delve into the types and mechanisms by which corruption has occurred (or occurs) in various social forestry activities. Tracking experience across several phases of social forestry, the corrupt practices were initially performed among the field foresters and the higher hierarchies. These corrupt practices were later imitated by other actors, who increasingly considered them as normal and acceptable practices. In contemporary social forestry programs, corruption is conducted by diverse stakeholders, including smallholder farmers, public officials and other authorities among the bureaucracy, as well as non-government organizations. Corruption has significant bearing on policy initiatives and programmatic outcomes, as it inhibits the implementation of formal rules and norms of social forestry. Our historical tracing provides better insights into why corruption is not only a social forestry-related challenge but also a part of a larger societal problem as it has been normalized and deepened over decades.